A numerical study on free vibration analysis of axial FGM beam. (2021) - Sharma, Pankaj; Singh, Rahul
Abstract: In present work, the generalized differential quadrature (GDQ) method is utilized to study the modal characteristics of clamped-clamped axially functionally graded (AFG) material beam. The modeling of AFG beam is carried out using Timoshenko beam theory. The material properties are assumed to vary in axial direction in accordance with power law distribution. The Hamilton's principle is used to derive the governing equations. The available partial differential equations are converted into linear algebraic form using generalized differential quadrature (GDQ) method. The results are validated with results obtained using different numerical techniques available in the literature for special cases. The effects of geometric parameters and volume fraction indices on natural frequencies are also presented.